Exploring Route for Pyrophosphate‐based Electrode Materials: Interplay between Synthesis and Structure. Issue 14 (16th July 2020) - Alekseeva, Anastasia M.; Tertov, Ilya V.; Mironov, Andrey V.; Mikheev, Ivan V.; Drozhzhin, Oleg A.; Zharikova, Emiliya V.; Rozova, Marina G.; Antipov, Evgeny V.
Abstract : New sodium vanadium(III) hydrogenphosphate hydrate NaV(HPO4 )2 (H2 O)0.5 and sodium vanadium(III) hydrogenphosphate β‐NaV(HPO4 )2 were prepared in mild hydrothermal conditions. The crystal structures of NaV(HPO4 )2 (H2 O)0.5 [space group Cc, Z = 4, a = 8.46174(19) Å, b = 9.52583(19) Å, c = 8.69376(15) Å, β = 110.9553(11) °, V = 654.41(2) Å 3 ] and β‐NaV(HPO4 )2 [space group C 2/ c, Z = 4, a = 7.8681(3) Å, b = 9.8451(3) Å, c = 8.5180(2) Å, β = 107.626(2) °, V = 628.85(3) Å 3 ] were solved and refined from X‐ray powder diffraction data. Both compounds were used as precursors in a new route for the preparation of attractive cathode material β‐NaVP2 O7 . The formation of the structure motive providing fast sodium ion diffusion at the first synthesis stage and its further conservation upon stepwise dehydration was revealed. The oversized Na + ‐embedding channels are stabilized by site‐coordinated water in NaV(HPO4 )2 (H2 O)0.5 structure. The topology resemblance and difference in known sodium vanadium(III) complex phosphates are discussed. Abstract :